Knockdown of AKR1C3 Promoted Sorafenib Sensitivity Through Inhibiting the Phosphorylation of AKT in Hepatocellular Carcinoma - Zheng, Jia; Yang, Zhihong; Li, Yanlei; Yang, Li; Yao, Ruili (Frontiers in Oncology, 2022)
Abstract Background Sorafenib, which can induce ferroptosis, is a multikinase inhibitor for enhancing survival in advanced HCC. However, a considerable challenge for the treatment of HCC is sorafenib resistance. Therefore, targeting the relationship between sorafenib resistance and ferroptosis genes may provide a novel approach for the treatment of HCC. Materials and methods We analyzed the gene expression and clinicopathology analysis from The Cancer Genome Atlas Liver Hepatocellular Carcinoma (TCGA-LIHC), International Cancer Genome Consortium (ICGC) and Gene Expression Omnibus (GEO) databases (GSE109211/GSE62813). The statistical analysis was conducted in R. Cell proliferation was assayed by MTT, cell colony-forming assay and wound healing assay. Immunofluorescence assay and western blot was used to evaluate the expression of AKT. Results Many ferroptosis-related genes were up-regulated in sorafenib resistant group. Aldo-keto reductase 1C3 (AKR1C3) was highly expressed in sorafenib-resistant patients and the high expression of AKR1C3 was associated with the poor prognosis of the patient from TCGA and ICGC database. MTT and colony-forming assay shown AKR1C3 overexpression enhanced the proliferation of HCC cells and acute sorafenib resistance. Knock-down AKR1C3 inhibited the proliferation of HCC cells and increase the drug sensitivity of sorafenib. Immunofluorescence assay and Western blot proved that AKR1C3 promoted the phosphorylation of AKT. Conclusion AKR1C3 can induce sorafenib resistance through promoting the phosphorylation of AKT in HCC. AKR1C3 inhibitors may be used in conjunction with sorafenib to become a better therapeutic target for HCC.